The effects of centralisation of school governance and funding on inequalities in education lessons from a policy reform in Hungary - Zoltán, Hermann,Semjén, András (Institute of Economics, Centre for Economic and Regional Studies, 2021)
In 2013 the responsibility for school governance and funding has been transferred from local governments to a central government agency in Hungary. The key objectives of this reform, as stated by policy makers, was to mitigate interjurisdictional inequalities in education. This paper explores whether the reform had an equalizing effect on education resources on the one hand, and student achievement on the other. First, we estimate elasticities of per-student school expenditures to average income in municipalities. The results reveal a substantial equalization of school resources: before the reform rich municipalities had spent significantly more on education than poor ones, while after the reform no difference in school spending can be detected. Second, we ask whether the equalization of resources had an effect on inequalities in student achievement. Student achievement is measured by test score in grade 6 and grade 8. The results show no equalization in this respect, suggesting that inequalities in school quality were hardly affected by the reform.
10419/256909
Keywords: Graue Literatur; centralisation; school governance; school finance; public management reform; inequality; student achievement